Use and Misuse of Serum Free Light Chain Assay: Challenging the Paradigms - Singh, Gurmukh (Archives of Clinical and Biomedical Research, 2025)
Introduction: Lympho-plasmacytic neoplasms produce monoclonal immunoglobulins that may be intact immunoglobulins, light chains only, or intact immunoglobulins plus free light chains. Plasma cells generally produce more light chains than heavy chains and excess free light chains are detectable in serum and urine. Assays specific for free light chains have been available for about 25 years. Observations and Interpretations: Monoclonal free light chains are pathogenic, whereas elevated polyclonal free light chains are markers of renal failure and inflammation. Abnormal ratio of serum free κ/⋌ chains has been used, erroneously, to diagnose monoclonal gammopathy. Urine examination is underutilized for evaluation of monoclonal free light chains. Diagnosis of monoclonal gammopathy of undetermined significance based on a κ/⋌ ratio of >1.65 has a 96% false positive rate; κ/⋌ ratio of >3.15 has a false positive rate of >80%. The requirement for a normal κ/⋌ ratio for stringent complete response is unsupported. Light chain escape in multiple myeloma probably does not exist. In monoclonal lesions, kappa chains occur at 4-5 times the concentration of lambda chains. Uninvolved kappa chains occur at twice the concentration of uninvolved lambda chains. Diagnostic criteria based on light chain quantity and ratio ought to be light chain type specific. The existing criterion for myeloma defining condition using light chain level of 100 mg/ dL and ratio of involved to uninvolved light chain levels of >100 is untenable. Light chain predominant lesions have significantly worse prognoses. Screening for monoclonal gammopathy of undetermined significance is contraindicated. Modified immunofixation electrophoretic analyses can detect monoclonal free light chains with the sensitivity of mass spectrometry. Recommendations: a) There is an urgent need for simple assays, suitable for use in routine clinical laboratories, for identification and quantification of free monoclonal light chains. b) Light chain predominant multiple myeloma lesions, both intact immunoglobulin as well as light chain only lesions, need to be identified as subtypes in clinical trials. Light chain predominant lesions have a 2-year shorter survival. c) High sensitivity immunofixation electrophoretic assays for monoclonal light chains in serum and urine ought to precede bone marrow examination in initial diagnosis as well as in monitoring of monoclonal gammopathic lesions. d) Abnormal κ/⋌ ratio is not diagnostic of monoclonal gammopathy and a normal ratio does not exclude monoclonal gammopathy. Diagnosis of a monoclonal gammopathic lesions ought to be supported by demonstration of a persistent, restricted mobility immunoglobulin in serum and/or urine, or a monoclonal population of plasma cells in bone marrow.